Pelatihan Kewirausahaan Budidaya Burung Puyuh pada Kelompok Belajar Usaha Citra Mandiri di Kabupaten Karawang - Puspitasari, Vita Oktaviani; Syahid, Ahmad (Journal of Nonformal Education and Community Empowerment, 2018)
The purpose of this study is to analyze the process, results, supporting factors and inhibiting factors of entrepreneurship training of quail cultivation at KBU Citra Mandiri Desa Bengle. The research approach is used with case study method. This research was conducted at KBU Citra Mandiri by determining five subjects of research consisting of one person organizer, one instructor and 3 learners. Instrument research using observation techniques, interviews and documentation studies. The stages in this research are: orientation stage, exploration stage, and member check stage. The results showed that the entrepreneurship training process of quail cultivation is motivated by efforts to improve the capability and human resources, especially the unemployed youth in Bengle Village. Training materials on the provision of facilities and equipment, seed procurement, quail maintenance, maintenance and harvesting and marketing. The methods used are lectures, demonstrations, frequently asked questions, discussions and practices. Training funds are obtained from the villages and from the dues of the residents of the learners. How to assess with written tests, oral tests and practice. The results of entrepreneurship training of quail cultivation shows, at least learners to cultivate the quail from the breeding process to marketing.